2012
DOI: 10.9735/0975-5276.4.6.253-257
|View full text |Cite
|
Sign up to set email alerts
|

INCREASING INCIDENCE OF MULTIDRUG RESISTANCE Klebsiella pneumoniae INFECTIONS IN HOSPITAL AND COMMUNITY SETTINGS

Abstract: Introduction-Klebsiella pneumoniae have been identified as an important common pathogen for nosocomial pneumonia (7 to 14% of all cases), septicaemia (4 to 15% of all cases), wound infections (2 to 4% of all cases), neonatal septicaemia (3 to 30% of all cases). It also causes bacteremia and hepatic infections and have been isolated from a number of unusual infections including endocarditis, primary gascontaining mediastinal abscess, cholecyctitis, diarrhoea, peritonitis, crepitant myonecrosis, pyomyositis, nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Klebsiella species showed 100% resistance to Ampicillin. Previous studies have shown similar resistance pattern with this drug (Jadhav et al, 2012). The chromosomally encoded β-lactamases could be responsible for this intrinsic resistance (Namratha et al, 2015).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Klebsiella species showed 100% resistance to Ampicillin. Previous studies have shown similar resistance pattern with this drug (Jadhav et al, 2012). The chromosomally encoded β-lactamases could be responsible for this intrinsic resistance (Namratha et al, 2015).…”
Section: Resultsmentioning
confidence: 60%
“…K. pneumoniae has been identified as an important common pathogen for nosocomial pneumonia, septicaemia and wound infections (Jadhav et al, 2012). Epidemic and endemic nosocomial infections caused by Klebsiella species are leading causes of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major problems of the world is antibiotic resistance in bacteria. The resistance to β-lactam antibiotics is usually provided by β-lactamases [1,2]. The development and rapid diffuse of phytopathogenic strains of P. aeruginosa and E. coli emerge as a very serious problem in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified as an important common pathogen which causes many diseases worldwide including community acquired pneumonia which remains one of the major causes of mortality even in developed countries. It is also a major nosocomial pathogen causing pneumonia, burn, wound infections, septicemia and urinary tract infections (1)(2)(3) . Treatment of K. pneumoniae infections has become very difficult especially in the last decades as the levels of antibiotic resistance are becoming increasingly very serious problem throughout the world.…”
Section: Introductionmentioning
confidence: 99%